2020
DOI: 10.1111/papr.12875
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Cultural Adaptation and Psychometric Properties of the European Portuguese Version of the Central Sensitization Inventory in Adolescents With Musculoskeletal Chronic Pain

Abstract: Background Central sensitization (CS) is an important feature in musculoskeletal chronic pain, and associated symptoms can be assessed using the Central Sensitization Inventory (CSI). Objectives This study aimed to translate and cross‐culturally adapt the CSI to the European Portuguese language and to assess its validity and reliability in adolescents with musculoskeletal chronic pain. Methods The European Portuguese version of the CSI was established following the translation and testing processes recommended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 61 publications
(93 reference statements)
3
11
1
Order By: Relevance
“…Support for the discriminant validity of the Serbian version of the CSI was provided by confirming the ability of total scores to discriminate among various types of chronically painful conditions and healthy controls, with presumably different levels of CS. Support for convergent validity of the CSI was provided by associations between CSI total scores, severity levels, and other CS‐related patient‐reported symptoms, including pain severity, sleep disturbance, cognitive functioning, pain catastrophizing, pain‐related fear‐avoidance beliefs, perceived level of disability, and perceived general mental and physical health, as has been found in previous studies 5–7 . The results of the present study provide additional support for the potential usefulness of the CSI in chronic pain assessment and treatment planning.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Support for the discriminant validity of the Serbian version of the CSI was provided by confirming the ability of total scores to discriminate among various types of chronically painful conditions and healthy controls, with presumably different levels of CS. Support for convergent validity of the CSI was provided by associations between CSI total scores, severity levels, and other CS‐related patient‐reported symptoms, including pain severity, sleep disturbance, cognitive functioning, pain catastrophizing, pain‐related fear‐avoidance beliefs, perceived level of disability, and perceived general mental and physical health, as has been found in previous studies 5–7 . The results of the present study provide additional support for the potential usefulness of the CSI in chronic pain assessment and treatment planning.…”
Section: Resultssupporting
confidence: 83%
“…The CSI has been psychometrically evaluated in English and other Asian, South American, and European languages. It has been found to be psychometrically sound in all published cross‐cultural studies to the present, with test‐retest reliability coefficients from 0.85 to 0.99 and Cronbach’s alpha from 0.88 to 0.99 5–7 . Evidence of convergent, discriminant, and predictive validity, using both subjective (eg, patient‐reported) and objective (including quantitative sensory testing, brain gamma aminobutyric acid levels, serum brain‐derived neurotrophic factor) CS‐related variables, have been found in a number of previous studies using multiple‐language versions of the CSI 5,8 .…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although it has a short, less than ten year history, the CSI has been translated and validated in adult populations into many languages, including Dutch [20], Spanish [21], Brazilian Portuguese [22], Gurajati [23], Serbian [24], French [25], Japanese [26], Greek [27], Nepalese [28], Russian [29], and Italian [30]. Additionally, the CSI has been validated in an adolescent population in European Portuguese [31]. Published results from previous cultural adaptations and validations suggest that the CSI is a reliable, valid, and consistent measure [32].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, CSS and catastrophic thinking were also associated with pain intensity [ 34 ], and the results of the amount of change in the present study showed a similar trend. In addition, previous cross-sectional studies have reported a correlation between CSI and PCS [ 43 , 44 ]. However, the change in CSS was not correlated with the change in catastrophic thinking.…”
Section: Discussionmentioning
confidence: 99%